Molluscum contagiosum/Multiple trichoepithelioma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2017)
Molluscum contagiosum is a very common infection caused by Pox virus that at least initially can simulate trichoepithelioma. Trichoepithelioma is a rare benign skin tumor with hair follicle differentiation; usually unique, it can present itself with multiple elements and in this case it is transmitted by an autosomal dominant trait.